The Interbank Market in Kenya: An Event-Based Stress Analysis Based on Treasury Bill Market - Osoro, Jared; Muriithi, David (European Scientific Journal, ESJ, 2017)
This paper seeks to explore nexus between the volatility in the Kenyan interbank market and Treasury bill market in the event of market distress arising from collapses of a lender. Three stress triggering events are defined; -the placement of Dubai Bank, Imperial Bank and Chase Bank placement under receivership. The inclusion of Treasury bill market is aimed to ascertaining whether then Central Bank’s intervention in the market to correct inefficiency in the interbank market upon the collapse of a lender is either proactive or reactive. The EGARCH and TGARCH were used to model the relationship. Key finding of the study is that 91-Day Treasury bill rate positively and significantly affects the interbank market rate with the effect doubling in the wake of bank collapse.